Allopatry, hybridization, and reproductive isolation in Arctostaphylos. Issue 12 (3rd December 2020) - Parker, V. Thomas; Rodriguez, Christina Y.; Wechsler, Gail; Vasey, Michael C.
Abstract : PREMISE: Hybridization plays a key role in introgressive adaptation, speciation, and adaptive radiation as a source of evolutionary innovation. Hybridization is considered common in Arctostaphylos, yet species boundaries are retained in stands containing multiple species. Arctostaphylos contains diploids and tetraploids, and recent phylogenies indicate two clades; we hypothesize combinations of these traits limit or promote hybridization rates. METHODS: We statistically analyzed co‐occurrence patterns of species by clade membership and ploidy level from 87 random 0.1 ha plots. We sampled multiple sites to analyze for percent hybridization based on morphology. Finally, phenophases were analyzed by scoring herbarium sheets for a large number of taxa from both clades as well as tetraploids, and second, surveying three field sites over two years for divergence in phenological stages between co‐occurring taxa. RESULTS: Most taxa in Arctostaphylos are allopatric relative to other congenerics. When two taxa co‐occur, the patterns are a diploid with a tetraploid, or two diploids from different clades. When three taxa co‐occur, the pattern is two diploids from different clades and a tetraploid. Field and herbarium data both indicate flowering phenology is displaced between diploids from the two clades; one of the diploid clades and tetraploids overlap considerably. CONCLUSIONS: The two deep clades in Arctostaphylos are genetically distant, with hybrids rare or non‐existent when taxa co‐occur. Reproductive isolation between clades is enhanced by displaced flowering phenology for co‐occurring species. Within clades, taxa appear to have few reproductive barriers other than an allopatric distribution or different ploidy levels.